Pemodelan Tsunami Menggunakan Sistem Informasi Geografis di Kecamatan Ambulu Kabupaten Jember - Emir Dienul Kukuh Prasetyo (Fakultas Teknik, 2023)
Jember Regency has 6 sub-districts prone to tsunami disasters, one of which is Kec. Ambulu. In 1994 it was discovered that 2 beaches in Ambulu District were affected by the tsunami disaster. The potential for a tsunami disaster on the coast of Ambulu District could affect the safety of tourists and coastal communities in Ambulu District. This research aims to carry out tsunami spatial modeling analysis and develop mitigation priorities. The method used is spatial analysis and Analytical Hierarchy Process (AHP). The results of this research showed that the tsunami collection area with a 4 meter wave scenario reached 219.09 ha, while the tsunami collection area with an 11 meter wave scenario reached 765.23 ha. The highest area of land use affected by the tsunami from the 2 scenarios is agricultural land with an area of 68.71 ha and 343.95 ha. The priority mitigation directions for the tsunami disaster in Ambulu District, Jember Regency are the use of tsunami dampening buildings and education, counseling and community awareness
Finalisasi_Maya_16 Juni 2026
Keywords: Tsunami Modeling; Mitigation Priorities; Analytical Hierarchy Process (AHP); Ambulu